Credit-based flow control for ATM networks credit update protocol, adaptive credit allocation and statistical multiplexing. - Kung, H.T (Computer communication review.)
This paper presents three new results concerning credit-based flow control for ATM networks: (1) a simple and robust credit update protocol (CUP) suited for relatively inexpensive hardware/software implementation; (2) automatic adaptation of credit buffer allocation for virtual circuits (VCs) sharing the same buffer pool; (3) use of credit-based flow control to improve the effectiveness of statistical multiplexing in minimizing switch memory. These results have been substantiated by analysis, simulation and implementation.